Modified Block Pulse Functions for Numerical Solution of Stochastic Volterra Integral Equations - K. Maleknejad; M. Khodabin; F. Hosseini Shekarabi (Journal of Applied Mathematics)
We present a new technique for solving numerically stochastic Volterra integral equation based on modified block pulse functions. It declares that the rate of convergence of the presented method is faster than the method based on block pulse functions. Efficiency of this method and good degree of accuracy are confirmed by a numerical example.